Development of Vocabulary Skills in Selected Second Year High School English Classes - Ong, Charito G. (JPAIR Multidisciplinary Research, 2009)
This study is on the development of vocabulary skills in selected second year high school English classes of San Isidro College, Malaybalay City. Specifically, it sought to answer four questions: when do teachers develop vocabulary, what are the teaching techniques employed by teaches to develop vocabulary, how do student react to the activities presented by the teacher and what behaviors are displayed by students to show that they understood the meanings of the new words developed by the teacher. An ethnographic approach to classroom observation was used for this study. The data were gathered through the use of cassette recorder and video tape. Actual observation was also conducted by the researcher to the sample classes. Findings revealed that the development of vocabulary skills was generally done at the start of the lesson. There were only few instances in which it was done at the middle of the discussion. Vocabulary was unlocked through the use of context clues which varies from semantic definition, explanation, description and appositive clues. Students enjoyed guessing the words’ meaning when used in context that choral responses were prevalent. They manifested that they understood the meanings of the new words developed by using the words in exact context during the lesson activities.